(untitled) (Ameghiniana, 2014)
Fragmentary anuran remains in the Ameghino Collection in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” were recently considered as belonging in Ceratophryidae (the clade of the South American horned frogs) and coming from middle–late Oligocene sediments exposed south of Lake Colhue Huapi, Chubut, Argentina. However, both the taxonomic placement and the geographic and stratigraphic origin attributed to this material are problematic. A new study of these remains show they possess several features that allow their attribution to the extant genus Ceratophrys Wied-Neuwied. The available information on the collection locality of this material is dubious –namely Gran Barranca, where rocks range from the middle Eocene to early Miocene in age. Additionally, details of the history of this collection and the specimen itself suggest that its provenance should better be considered unknown.